Minat dan Motivasi Belajar Mahasiswa pada Mata Kuliah Makanan Asia Program Studi Pendidikan Tata Boga: Penelitian - Tri Wahyuni Indah Permata; Isa Ansori (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study was conducted to obtain an overview of students’ learning interest and learning motivation in the Asian Cuisine course among 2024 cohort students of the Culinary Education Study Program at Universitas Negeri Surabaya during their third semester. This study is grounded in the limited availability of empirical research that specifically examines learning interest and motivation in skill-based courses within Culinary Education, particularly the Asian Cuisine course, which is practical in nature and rooted in culinary culture. The study employed a quantitative approach with a descriptive design and involved 189 students as respondents using a total sampling technique. Data were collected through learning interest and learning motivation questionnaires that had met reliability criteria. The data were analyzed descriptively using mean scores and category distributions. The results indicate that students’ learning interest was in the high category, with a mean score of 3.78 and a percentage of 69.8%, while learning motivation was also categorized as high, with a mean score of 3.65 and a percentage of 62.4%. The novelty of this study lies in its presentation of empirical evidence that specifically describes students’ learning interest and motivation in the Asian Cuisine course within the context of Culinary Education, which can serve as a basis for developing more contextual, relevant, and quality-oriented instructional strategies in vocational culinary education.